Environmental Management in Reducing the Impact of Company Operations on Ecosystems - Situmorang, Marningot (CV. HEI PUBLISHING INDONESIA, 2024)
This article discusses environmental management strategies in reducing the impact of company operations on ecosystems. Against the backdrop of increasing environmental damage due to carbon emissions, toxic waste, and ecosystem degradation, this article examines the concept and implementation of environmental management through a qualitative descriptive method. The study uses secondary data from scientific journals, books, and company reports to analyze the steps taken by companies in implementing environmentally friendly policies. The results show that the implementation of clean technology, energy efficiency, circular economy-based waste management, and collaboration with stakeholders significantly reduce environmental impacts. Case studies from PT Pertamina Geothermal Energy and PT Semen Indonesia Tbk show success in reducing carbon emissions by 150,000 tons and 2 million tons of CO2 per year, respectively. In addition, the use of alternative fuels and waste recycling are effective solutions to reduce dependence on fossil fuels. This article emphasizes the importance of green technology investment, public awareness raising, and cross-sector collaboration to support environmental sustainability. Thus, environmental management is not only a corporate obligation but also a strategic opportunity to improve operational efficiency and business reputation.